6-11n=50

Simple and best practice solution for 6-11n=50 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-11n=50 equation:



6-11n=50
We move all terms to the left:
6-11n-(50)=0
We add all the numbers together, and all the variables
-11n-44=0
We move all terms containing n to the left, all other terms to the right
-11n=44
n=44/-11
n=-4

See similar equations:

| 5m+3=23.m= | | 7(3w+6)^5=-7 | | 7(3w+6)^5=-7 | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6m+2-4m=2(-m+2) | | 6y+8=5y+10 | | 6y+8=5y+10 | | 6y+8=5y+10 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | x4+-3x2-10=0 | | y-11=3y-11 | | w/0.197=7.8 | | 5x10=-44-4x | | –k=–217 | | 7e+3.3=0.3 | | 3-6y=144 | | -6x^2-16x-8=0 | | –12=3(d+9) | | –12=3(d+9) | | –12=3(d+9) | | 1/3x−9=15 |

Equations solver categories